Positive Carotenoid Balance Correlates with Greater Reproductive Performance in a Wild Bird - Safran, Rebecca J. (Public Library of Science, 2010)
BACKGROUND: Carotenoids can confer somatic and reproductive benefits, but most evidence is from captive animal experimentation or single time-point sampling. Another perhaps more informative means by which to assess physiological contributions to animal performance is by tracking an individual's ability to increase or sustain carotenoids or other health-related molecules over time, as these are likely to be temporally variable. METHODOLOGY/PRINCIPAL FINDINGS: In a field study of North American barn swallows (Hirundo rustica erythrogaster), we analyzed within-individual changes in carotenoid concentrations by repeatedly sampling the carotenoid profiles of individuals over the course of the breeding season. Our results demonstrate that carotenoid concentrations of individuals are temporally dynamic and that season-long balance of these molecules, rather than single time-point samples, predict reproductive performance. This was true even when controlling for two important variables associated with reproductive outcomes: (1) timing of breeding and (2) sexually selected plumage coloration, which is itself positively correlated with and concomitantly changes with circulating carotenoid concentrations. CONCLUSIONS/SIGNIFICANCE: While reproduction itself is purported to impose health stress on organisms, these data suggest that free-ranging, high-quality individuals can mitigate such costs, by one or several genetic, environmental (diet), or physiological mechanisms. Moreover, the temporal variations in both health-linked physiological measures and morphological traits we uncover here merit further examination in other species, especially when goals include the estimation of signal information content or the costs of trait expression.